A Direct Ammonia Fuel Cell with a KOH-Free Anode Feed Generating 180 mW cm−2 at 120 °C. Issue 13 (14th October 2020) - Achrai, Ben; Zhao, Yun; Wang, Teng; Tamir, Gal; Abbasi, Reza; Setzler, Brian P.; Page, Miles; Yan, Yushan; Gottesfeld, Shimshon
Abstract : The motivations to operate the direct ammonia fuel cell (DAFC) with no addition of aqueous base, include facilitated fuel management and prevention of corrosion and shunt currents in the DAFC stack. We describe here a polymer electrolyte DAFC, operating at a cell temperature (Tcell ) of 120 °C on ammonia and water alone as anode feed, that demonstrated peak power of 180 mW cm −2 —a record for this type of fuel cell. We offer a detailed analysis of polarization curves recorded for PE-DAFCs in the Tcell range of 60 °C–120 °C, allowing to estimate the effects of KOH-free operation on the ionic and faradaic resistances, R i and R F, that determine together the value of R app, CL – an, the apparent resistance of the anode catalyst layer. The latter resistance drops ten times between 60 °C and 120 °C as result mainly of the drop in R F . Consequently, DAFC performance at Tcell > 100 °C improves substantially, including the cell performance on a KOH-free anode feed. The demsontrated performance levels reported here for KOH-free DAFCs support further development of this type of ammonia/air fuel cells.